Self Expression Lyrics of Yura Yunita's Song Tenang: Van Dijk's Critical Discourse - Nella Viana Nur Ramadhanti; Abrian, Rizky (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to reveal that self-expression in the song lyrics can influence people's views on the issues they experience contained in the lyrics of Yura Yunita's song "Tenang". In the meaning of the song, the lyrics of the song "tenang" represent the life experiences experienced by Yura Yunita when she felt the anxiety that hit her. The method used in this research is using a qualitative descriptive method. This research uses data collection and analysis techniques by looking at the song lyrics on the website, then using Spotify to listen to a calm song and then watching the music video on Yura Yunita's YouTube account. In the process of data analysis, the lyrics of the calm song were absorbed and then the results were presented which were linked to Van Dijk's critical discourse analysis theory. This research uses Van Dijk's theory of critical discourse analysis which consists of macro structure, superstructure and micro structure which includes (semantics, syntax, stylistics and rhetoric). This discourse analysis also analyzes social cognition and social context in the lyrics of the song "tenang ” Yura Yunita. The result of this research is an explanation of self-expression in the lyrics of Yura Yunita's song "Tenang".